The Aftermaths of Participation Outcomes and Consequences of Participatory Work with Forced Migrants in Museums - Boersma, Susanne (Edition Museum, 2022)
How do participatory museum projects with forced migrants impact both the museum and the participants? What happens during these projects and what is left of them afterwards? Based on interviews with museum practitioners, facilitators and project participants, Susanne Boersma brings together unique insights into museum work with forced migrants. Her study of participatory projects in Germany, the Netherlands and the UK reveals museums' limiting infrastructures, the shortcomings of their ethical frameworks, and the problems of addressing forced migrants as 'communities'. Outlining the diverging objectives, experiences and outcomes of participatory projects, she suggests how these might be united in practice.